Semi-analytical model for the determination of vertical settlement of crest of road embankments founded on sloping ground - Pantelidis, Lysandros (My University, 2010)
Instabilities that follow the pattern of local translational sliding are rather common along old highway embankments founded on natural slopes, mainly in mountainous terrains. In this paper a semi-analytical model for the determination of the vertical settlement of crest of non-cohesive road embankments founded on sloping ground is presented. The model is based on the principal of conservation of energy, where the change of the potential energy of the sliding mass between its initial and final position is taken as equal to the energy dissipated in deformation, that is, in grain to grain friction inside the body of the embankment and along its base. According to the proposed methodology, the vertical settlement Δy of crest results proportionally to the deformation velocity of embankment mass. The mean value of the maximum velocities of embankment grains acquired during sliding is used. The last is obtained from a proposed empirical diagram, the magnitude of which depends on the embankment height, the gradient of natural base and the unit weight and particle size distribution of the embankment material.
Keywords: Road embankment; Vertical settlement; Sloping ground; Rheological model; Local failure; Translational sliding